Training and Mentoring in Creating Website-Based Student Learning Spaces Using Google Sites - Fauzi, Moch.; Likasari, Gati Ayu; Ayuningtyas, Triwilujeng; Halim, Fahmi Abdul (PT. Anagata Sembagi Education, 2025)
The majority of elementary school, MI, MTs, MA teachers in Bago Village, Pasirian District, Lumajang Regency still provide material traditionally, namely using textbooks as learning resources. In fact, we have now entered the modern era, namely the era of technology. The use of technology such as digital applications makes the appearance of teaching materials better, more real, and more attractive. Activities are urgently needed to improve teachers' soft skills in mastering website-based learning space creation applications using Google Site so that the skills of integrating technology into learning materials also increase. The implementation of this community service uses training and mentoring methods for community service partners, namely elementary school, MI, MTs, MA teachers in Bago Village, Pasirian District, Lumajang Regency in the odd semester of 2024/2025. The training was carried out face-to-face (offline) and mentoring was carried out directly at SD Negeri Bago 3 to practice using the website-based Google Site. The results of the community service showed an increase in the mastery of the concept of